Impulsive UV-pump/X-ray probe study of vibrational dynamics in glycine. Issue 1 (December 2018) - Mincigrucci, Riccardo; Kowalewski, Markus; Rouxel, Jérémy; Bencivenga, Filippo; Mukamel, Shaul; Masciovecchio, Claudio
Abstract We report an ab-initio study of a pump-probe experiment on the amino-acid glycine. We consider an UV pump followed by an X-ray probe tuned to carbon K-edge and study the vibronic structure of the core transition. The simulated experiment is feasible using existing free electron laser or high harmonic generation sources and thanks to the localization of the core orbitals posseses chemical selectivity. The present theory applies to other experimental schemes, including the use of a THz probe, available with present soft X-ray free electron lasers and/or high harmonic generation sources.